Pengaruh Bid-Ask Spread, Market Value, Variance Return, Dan Earnings Per Share Terhadap Holding Period Saham Pada Indeks Saham Syariah Indonesia Periode 2015-2018 - Yesika Yanuarisa (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This study aims to analyze the effect of bid-ask spread, market value, variance return, and earnings per share on stock holding period. The population in this study is the company’s share listed on the Indonesia Sharia Stock Index for the 2015-2018 period. Samples were selected using the purposive sampling method so that 88 company shares were obtained as samples. This research is a type of quantitative research. The analytical method in this study is multiple linear regression analysis, which  firstly tested  the classical assumption test using IBM SPSS Statistics 24 software. Based on the test results showed that partially market value, variance return, and earnings per share have effect on stock holding period, and bid-ask spread have no effect on stock holding period. While simultaneously bid-ask spread, market value, variance return, and earnings per share have effect on stock holding period.